2012
DOI: 10.1179/1743290112y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of injection moulded Nimonic-90 superalloy parts

Abstract: This study aims to determine optimum sintering and heat treatment parameters of powder injection moulded Nimonic-90 powder parts. Determination of optimum heat treatment conditions for sintered parts aimed to achieve maximum densities, and the microstructure and mechanical properties of the produced parts were characterised in sintered and heat treated conditions. Injection moulding feedstock was prepared by mixing Nimonic-90 powder with a multicomponent binder system. After moulding, the samples were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…Thus, varying contributions to the hardness are dominant at different sintering conditions and are visible in the density measurements, OM and SEM/EDS observations. Similar results were reported by Ozgun et al for traditionally-manufactured Nibased superalloys [12,18,24,25].…”
Section: Mechanical Properties 351 Microhardnesssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, varying contributions to the hardness are dominant at different sintering conditions and are visible in the density measurements, OM and SEM/EDS observations. Similar results were reported by Ozgun et al for traditionally-manufactured Nibased superalloys [12,18,24,25].…”
Section: Mechanical Properties 351 Microhardnesssupporting
confidence: 91%
“…It is reported that a relative density of 96% with an average particle size of 12.5 μm as a result of sintering performed for 2 h in 5% hydrogen and argon at 1235 °C [26]. A difference in the obtained results in this study is due to the larger particle size used, since the driving force of sintering is a decrease in surface energy [18,25]. Ozgun et al reported that powder injection molded alloy 625 powders with the average particle size of 11.1 μm sintered at 1300 °C for 3 h resulted in 98% density.…”
Section: Density Measurementscontrasting
confidence: 70%
“…The lattice misfit is used to evaluate the strain state at the interfaces of phases, which greatly influences the high-temperature properties of superalloys. It is generally believed that in the high-temperature creep tests, a higher microstructure stability is expected when the misfit between phases is smaller [33,34]. Due to the expanding of γ lattice, the misfits between γ’’ and γ became larger with increasing solution temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, PIM of superalloys has attracted great attention for a variety of gas turbine engine parts [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%